1992
DOI: 10.1303/jjaez.36.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insecticides on the Serpentine Leafminer, Liriomyza trifolii (BURGESS) (Diptera: Agromyzidae).

Abstract: An outbreak of the serpentine leafminer, Liriomyza trifolii (BURGESS) occurred on many ornamental crops and vegetables in the spring of 1990 in Shizuoka Prefecture, Japan. The fly proved impossible for growers to control with conventional insecticides. Insecticides were evaluated for control of the fly on a bean (Phaseolus vulgaris L.) in the laboratory.Among 54 insecticides tested by spraying on one-day-old larvae, isoxathion, thiocyclam, cartap, cyromazine, and flufenoxuron gave high mortality.The LC50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The effectiveness of dimethoate was high for the Kagoshima population, but low for the Shizuoka population. Flufenoxuron, which was effective on L. trifolii (Saito et al, 1992(Saito et al, , 1996, was less effective for the tested populations of C. horticola. It must be noted that emamectin-benzoate (Saito, 1997) and cyromazine (Parrella and Keil, 1984;Trumble, 1985;Saito et al, 1992), which are effective on L. trifolii, and fipronil, spinosad and chlorfenapyr, which are new insecticides, were highly effective on C. horticola.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The effectiveness of dimethoate was high for the Kagoshima population, but low for the Shizuoka population. Flufenoxuron, which was effective on L. trifolii (Saito et al, 1992(Saito et al, , 1996, was less effective for the tested populations of C. horticola. It must be noted that emamectin-benzoate (Saito, 1997) and cyromazine (Parrella and Keil, 1984;Trumble, 1985;Saito et al, 1992), which are effective on L. trifolii, and fipronil, spinosad and chlorfenapyr, which are new insecticides, were highly effective on C. horticola.…”
Section: Discussionmentioning
confidence: 87%
“…Of the insecticides, however, only isoxathion showed a high effectiveness in the Shizuoka and Kagoshima populations with 31.2 ppm and 10.8 ppm of LC 50 , respectively, in the present assay. Saito et al (1992) found that isoxathion was a unique organophosphate with a high effectiveness (33 ppm of LC 50 ) to L. trifolii, which was resistant to organophosphates. However, the mechanism of high effectiveness of isoxathion on such leafminers remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Because L. trifolii had already acquired a high resistance to many insecticides (Parrella, 1987;Saito et al, 1992), chemical control often caused rapid growth of the pest population due to an adverse impact upon native natural enemies (Saito et al, , 1996. Two European species of parasitoid, Diglyphus isaea (Walker) and Dacnusa sibirica Telenga, have been introduced to Japan as an alternative control measure (Ozawa et al, 1993(Ozawa et al, , 1999Tatara et al, 1993;Saito et al, 1995;Ichikawa et al, 1996;Shibao et al, 1996;Matsumura et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…All three leafminers have developed high levels of resistance to a range of chemical insecticides (e.g. Parrella and Keil, 1984;Saito et al, 1992;Saito, 2004;Ohta et al, 2005;Tokumaru et al, 2005), but insecticides do eliminate local parasitoids, leading to pest resurgence, suggesting that parasitoids may be important natural enemies of leafminers under insecticide-free conditions (e.g. Oatman and Kennedy, 1976;Schuster and Price, 1985;Saito et al, 1996;Saito, 2004).…”
Section: Introductionmentioning
confidence: 99%